Coxiella burnetii and Francisella tularensis in wild small mammals from the Czech Republic - Bártová, Eva; Kučerová, Hana Lya; Žákovská, Alena; Budíková, Marie; Nejezchlebová, Helena (Ticks and tick-borne diseases, 2020)
Wild rodents are an important source of the tick-borne pathogens Coxiella burnetii and Francisella tularensis. The aim of our study was to assess the prevalence of antibodies and possible coexistence of these pathogens in wild small mammals from three localities in the Czech Republic. A total of 614 wild small mammals (324 Apodemus flavicollis, 145 Myodes glareolus, 50 Sorex araneus, 48 A. sylvaticus, 40 A. agrarius, six Microtus arvalis and one Talpa europaea) were trapped between 2012 and 2015. Their sera or heart extracts were examined by modified indirect enzyme-linked immunosorbent assay, with the detection of antibodies against C. burnetii and F. tularensis in 12 % and 7 % of animals, respectively; coinfection was identified in 4.4 % of animals. The prevalence of C. burnetii and F. tularensis antibodies statistically differed according to animal species and sex (p < 0.05); the seroprevalence of C. burnetii (p < 0.05) also differed in the sampling period. The highest prevalence of antibodies against C. burnetii and F. tularensis was detected in the case of M. glareolus (24 % and 14 %, respectively).
Keywords: protilátky bakteriální; Prevalence; Coxiella burnetii; Arvicolinae; Moles; Česká republika; Q Fever; Q-horečka; krtci; rejskovití; Q fever; Serology; mužské pohlaví; prevalence; Francisella tularensis; tularemie; Czech Republic; Murinae; ženské pohlaví; Shrews; zvířata; Myodes; Seroepidemiologic Studies; Antibodies, Bacterial; koinfekce; Apodemus; séroepidemiologické studie; Coinfection; Tularemia; Female; Male; Animals